2011
DOI: 10.1016/s1470-2045(11)70012-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between miR-200c and the survival of patients with stage I epithelial ovarian cancer: a retrospective study of two independent tumour tissue collections

Abstract: Nerina and Mario Mattioli Foundation, Cariplo Foundation (Grant Number 2010-0744), and the Italian Association for Cancer Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(150 citation statements)
references
References 33 publications
8
140
0
2
Order By: Relevance
“…In the present study, we focused on miR-214, which displays complex and contrary behavior in ovary cancers. miR-214 is overexpressed in ovary cancers and significantly associated with high grade and late/metastatic tumor stages, as well as with overall and progression free survival and post-surgical/chemotherapy recurrence [17,26,27]. However, miR-214 down-regulation has also been reported in neoplastic, as compared with normal ovaries, as well as in ovary cancer-derived effusions as compared with primary tumors [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we focused on miR-214, which displays complex and contrary behavior in ovary cancers. miR-214 is overexpressed in ovary cancers and significantly associated with high grade and late/metastatic tumor stages, as well as with overall and progression free survival and post-surgical/chemotherapy recurrence [17,26,27]. However, miR-214 down-regulation has also been reported in neoplastic, as compared with normal ovaries, as well as in ovary cancer-derived effusions as compared with primary tumors [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In some tumors, up-or downregulation of miR-200c was correlated with poor outcome. For instance, downregulation of miR-200c was correlated with relapse in stage I epithelial ovarian cancers (16) and other tumors of the female reproductive organs (17). Likewise, a reduction of this miRNA correlated with a more aggressive behavior of non-small-cell lung cancer (18) whereas lung mesotheliomas or pancreatic carcinomas in contrast exhibit increased levels of miR-200c (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Like this article, other three studies estimated the prognostic value of miRNA 200c expression in tumor tissue (Yu et al, 2010;Marchini et al, 2011;Karaayvaz et al, 2012). Among these studies, two studies reported HR and its 95% CI (Marchini et al, 2011;Toiyama et al, 2013) and the rest ones were processed by Matthew Sydes and Jayne Tierney's method to acquire survival data (Tierney et al, 2007;Marchini et al, 2011;Karaayvaz et al, 2012). HRs (high vs low) were pooled by fixedeffects model ( Figure 2B, …”
Section: Tissue Mirna 200c Expression and Survivalmentioning
confidence: 98%